Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Review: 84

Answer

3x(x-9)(x-1)

Work Step by Step

3$x^{3}$-30$x^{2}$+27x=3x($x^{2}$-10$x^{}$+9)= 3x($x^{2}$-1x-9x+9)=3x[x(x-1)-9(x-1)]= 3x(x-9)(x-1)
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.